2018
DOI: 10.1186/s12915-018-0616-2
|View full text |Cite
|
Sign up to set email alerts
|

Homology-independent multiallelic disruption via CRISPR/Cas9-based knock-in yields distinct functional outcomes in human cells

Abstract: BackgroundCultured human cells are pivotal models to study human gene functions, but introducing complete loss of function in diploid or aneuploid cells has been a challenge. The recently developed CRISPR/Cas9-mediated homology-independent knock-in approach permits targeted insertion of large DNA at high efficiency, providing a tool for insertional disruption of a selected gene. Pioneer studies have showed promising results, but the current methodology is still suboptimal and functional outcomes have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Large DNA elements can also be inserted in target genes without homology arms, known as homology-independent insertion (Cristea et al 2013;Maresca et al 2013;Katic et al 2015;Lackner et al 2015;Schmid-Burgk et al 2016;Suzuki et al 2016;Katoh et al 2017;Kumagai et al 2017;Zhang et al 2018;Gao et al 2019). In this method, simultaneous cutting of a circular donor plasmid and a genomic target site by a nuclease results in integration of linearized insert DNA into the genomic cut site by nonhomologous end joining (NHEJ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Large DNA elements can also be inserted in target genes without homology arms, known as homology-independent insertion (Cristea et al 2013;Maresca et al 2013;Katic et al 2015;Lackner et al 2015;Schmid-Burgk et al 2016;Suzuki et al 2016;Katoh et al 2017;Kumagai et al 2017;Zhang et al 2018;Gao et al 2019). In this method, simultaneous cutting of a circular donor plasmid and a genomic target site by a nuclease results in integration of linearized insert DNA into the genomic cut site by nonhomologous end joining (NHEJ).…”
mentioning
confidence: 99%
“…For example, donor DNA can insert in two directions, insertion/deletion mutations (indels) at the integration site can affect the insert translation frame, the entire plasmid can integrate, and inserts can form concatemers. Nevertheless, for some targeting strategies such as C-terminal protein tagging or gene disruption, homology-independent insertion has been shown to be a fast, simple, and effective alternative to HDR in human cell lines (Cristea et al 2013;Maresca et al 2013;Lackner et al 2015;Schmid-Burgk et al 2016;Katoh et al 2017;Zhang et al 2018), mouse somatic cells (Suzuki et al 2016;Gao et al 2019), zebrafish , Caenorhabditis elegans (Katic et al 2015), and Daphnia (Kumagai et al 2017). However, this method has not yet been utilized in Drosophila.…”
mentioning
confidence: 99%
“…In 2014, Auer et al exploited the NHEJ mechanism to capture large DNA at Cas9-induced DSB sites and established a distinct homology-independent knock-in approach [ 110 ]. In 2016, He et al compared the NHEJ- and HDR-mediated knock-in side-by-side in various human cell types using a promoterless GFP reporter system and found that the homology-independent knock-in via NHEJ repair mechanism showed superior efficiency compared to HDR methods [ 111 , 112 ]. This is consistent with the understanding that HDR is associated with DNA replication, while the NHEJ mechanism adopts a more flexible process that is largely active throughout the cell cycle [ 113 ].…”
Section: Advancement Of In Vivo Gene Editing Using Aav-delivered Nuclmentioning
confidence: 99%
“…They found that the NHEJ pathway mediated homology‐independent knock‐in at previously unattainable high efficiencies, which was superior to commonly used HDR methods in all human cell lines examined . Subsequently, Zhang et al have applied this strategy to trace and enrich gene disruption in hyperploid somatic cell lines; and Suzuki et al applied this strategy for in vivo transgene integration, which has directed its application for genome editing‐based therapy. It is noteworthy that NHEJ‐mediated knock‐in introduces desired modifications as well as reversely oriented insertions, and it yields indels at integration junctions, which should be taken into consideration to prevent unwanted outcome in subsequent applications.…”
Section: High‐efficiency Genome Editing and New Applications Enabled mentioning
confidence: 99%
“…Up to now, sgRNA libraries have been constructed for both human and murine models, with target sites not only in the coding but also in the non‐coding regions . Future research might solve the systemic limitations such as restrictions due to PAM requirements, challenges for working with hyperploid cell models to generate loss‐of‐function phenotypes and compensatory effects introduced by survival stress when an essential gene is knocked out …”
Section: High‐efficiency Genome Editing and New Applications Enabled mentioning
confidence: 99%